Modelling magnetic levitation (maglev) train - Mohd Firdaus, Bajuri (2012)
"Maglev‟ represents magnetic levitation. The magnetically levitated train has no wheels, but floats on an electromagnetic wave. Maglev is trains that run on magnets in a certain way so that they are equally levitated. Maglev trains prove to be a promising technology in the future. The transrapid system uses servo mechanism to pull the train up from underneath the track and maintains a constant gap while travelling at high speed. Magnetically levitated trains may be the transportation of the future because of their advantages on modern transportation use today. As the train floats on the track, there is no contact with ground and need no moving parts, making the train a low maintenance affair. Their maintenance is less expensive than the conventional trains. Furthermore, there is no possibility of any parts wearing out and there is less noise because no steels wheels running on steel tracks. However, noise still occurred by air resistance. They are a lot better than the trains we used today and run almost as fast as an airplane. Also, these trains run on magnets, and therefore do not produce pollution, making them much more environmentally safe.